Media and memory - Garde-Hansen, Joanne 1975- (Edinburgh University Press, 2011)
How do we rely on media for remembering? In exploring the complex ways that media converge to support our desire to capture, store and retrieve memories, this textbook offers analyses of representations of memorable events, media tools for remembering and forgetting, media technologies for archiving and the role of media producers in making memories. Theories of memory and media are covered alongside an accessible range of case studies focusing on memory in relation to radio, television, pop music, celebrity, digital media and mobile phones. Ethnographic and production culture research, including interviews with members of the public and industry professionals, is also included. Offering a comprehensive introduction to the connections and disconnections in the study of media and memory, this is the perfect textbook for media studies students